Enhancing peroral cholangiopancreatoscopy with concurrent video-rate fluorescence imaging - Glatz, Jürgen; Garcia-Allende, P. Beatriz; Becker, Valentin; Koch, Maximilian; Meining, Alexander; Ntziachristos, Vasilis (Optical Molecular Probes, Imaging and Drug Delivery, OMP 2013, 2013)
Fluorescence imaging plays an increasingly important role for the interventional identification and demarcation oftumor by visualizing molecular biomarkers. We showcase the usage of indocyanine green (ICG) for enhancing endoscopy of the pancreaticobiliary ducts in patients. ©2013 The Optical Society (OSA).
CRIS-Team Scopus Importer:2023-03-08